2020
DOI: 10.1080/10503307.2020.1823029
|View full text |Cite
|
Sign up to set email alerts
|

Cross-trial prediction in psychotherapy: External validation of the Personalized Advantage Index using machine learning in two Dutch randomized trials comparing CBT versus IPT for depression

Abstract: Optimizing treatment selection may improve treatment outcomes in depression. A promising approach is the Personalized Advantage Index (PAI), which predicts the optimal treatment for a given individual. To determine the generalizability of the PAI, models needs to be externally validated, which has rarely been done. Method: PAI models were developed within each of two independent trials, with substantial between-study differences, that both compared CBT and IPT for depression (STEPd: n = 151 and FreqMech: n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 52 publications
(69 reference statements)
6
31
0
2
Order By: Relevance
“…Interestingly, empirical studies found effects that are comparable to the standard deviation of individual treatment effects. For example, after cross-validating a method that matches patients to either cognitive-behavioural therapy or interpersonal psychotherapy, Van Bronswijk et al 25 found that patients matched to their optimal treatment scored about 2 points or 9.1% lower on the BDI-II. Following a similar approach, Schwartz and colleagues 26 reported 14.2% lower symptom severity on the Brief Symptom Inventory for the subgroup of patients that were predicted to benefit most from either CBT or PDT, which corresponds to a small effect (Cohen's d = 0.33), which is corroborated by another study that found a difference of 2.6 points on the HDRS 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, empirical studies found effects that are comparable to the standard deviation of individual treatment effects. For example, after cross-validating a method that matches patients to either cognitive-behavioural therapy or interpersonal psychotherapy, Van Bronswijk et al 25 found that patients matched to their optimal treatment scored about 2 points or 9.1% lower on the BDI-II. Following a similar approach, Schwartz and colleagues 26 reported 14.2% lower symptom severity on the Brief Symptom Inventory for the subgroup of patients that were predicted to benefit most from either CBT or PDT, which corresponds to a small effect (Cohen's d = 0.33), which is corroborated by another study that found a difference of 2.6 points on the HDRS 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies since then have tried to predict which evi dencebased psychotherapy is most likely to benefit a specific patient 55,59 , including efforts to identify which of two (or more) psychotherapies may be most effective 60,61 , and whether a given patient is predicted to respond better to psychotherapy or medi cations 56 . A recent scoping review 62 identified a total of 44 studies that developed and tested a machine learning model in psycho therapy, but only seven of them reported on the feasibility of the tool.…”
Section: Psychotherapiesmentioning
confidence: 99%
“…PAIstyle approaches that calculate treatment by variable in teractions quickly lead to highdimensionality prediction analy ses that are prone to overfitting (or require very large sample sizes). Using data from two Dutch randomized trials, van Bron swijk et al 60 examined whether PAI models developed in one clinical trial dataset were able to successfully generalize to an independent dataset. Although the models performed statisti cally above chance in the trial used to train them, they did not generalize to the other clinical trial when predicting benefit for CBT versus interpersonal therapy (IPT) for depression.…”
Section: Psychotherapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent publication (Bruijniks et al, 2020), we used machine-learning methods to conduct a similar analysis, still finding large effects of the PTR on those assigned to their optimal vs. non-optimal treatment (d =0.57). Nonetheless, when we applied that prediction model to data from another trial (van Bronswijk et al, 2020), the observed advantage of the multivariable moderator was small (d =0.16); the effect size shrank over 77% of its original size.…”
Section: Is It the Size Or Is It The Fit?mentioning
confidence: 99%